Local bond-slip behaviour of reinforcing bars in fibre reinforced lightweight aggregate concrete at ambient and elevated temperatures - Kevinly, Christopher (2023)
This paper presents an experimental investigation of the bond-slip behaviour of reinforcing bars in fibre-reinforced lightweight aggregate concrete (FRLWAC) at ambient and elevated temperatures. Sixty-four bond-slip specimens with four target temperature exposures, two concrete covers and four steel fibre contents were tested to failure. The experimental results showed that exposure to elevated temperature shifted failure pattern from more ductile pull-out to brittle splitting modes, and reduced the peak bond strength and toughness of bond-slip behaviour. Scanning electron microscope (SEM) images of the concrete-steel interface showed that thermal mismatch induced microcracks contributed to degradation of bond strength, in addition to temperature induced degradation of concrete materials. The temperature exposure also negated beneficial effect of concrete cover in enhancing bond behaviour. Addition of steel fibre helped in preventing brittle failure mode, enhancing bond strength in specimens with small concrete cover and improving the post-peak bond-slip behaviour at all target temperatures. A simple semi-analytical bond-slip model that considers different failure modes and incorporates fibre-reinforced concrete tensile behaviour from Swedish Code SS 812310 was proposed and validated based on the test results in this study.